1997
DOI: 10.1002/art.1780400322
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells as target for antiphospholipid antibodies. Human Polyclonal and Monoclonal Anti‐β2‐Glycoprotein I Antibodies React In Vitro with Endothelial Cells Through Adherent β2‐Glycoprotein I and Induce Endothelial Activation

Abstract: Objective. To investigate the ability of human anti-&-glycoprotein I (anti-&GPI) antibodies to recognize the cofactor adherent on endothelial cells (EC) and to modulate endothelial functions.Methods. Six human affinity-purified polyclonal anti-P,GPI IgG and 2 IgM monoclonal antibodies (MAb) were obtained from patients with the antiphospholipid syndrome. The antibodies were tested for their ability to 1) bind to endothelial monolayers through the adherent f3,GPI and 2) modulate endothelial adhesion molecule exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
142
0
5

Year Published

1998
1998
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(158 citation statements)
references
References 45 publications
5
142
0
5
Order By: Relevance
“…Several studies have demonstrated that aPL activate ECs in vitro, suggesting a mechanism by which these antibodies exert procoagulant properties (15,49,50). Utilizing a mouse model, our group has previously demonstrated that aPL antibodies increase leukocyte adhesion to ECs of cremasteric muscle postcapillary venules, suggesting that these antibodies induce activation of ECs in vivo and that these effects correlate with enhanced thrombus formation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that aPL activate ECs in vitro, suggesting a mechanism by which these antibodies exert procoagulant properties (15,49,50). Utilizing a mouse model, our group has previously demonstrated that aPL antibodies increase leukocyte adhesion to ECs of cremasteric muscle postcapillary venules, suggesting that these antibodies induce activation of ECs in vivo and that these effects correlate with enhanced thrombus formation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Some aPL bind to endothelial cells, suggesting that aPL may interact with endothelial cells and thus promote thrombosis (68,69). APTs can bind to immobilized PS in the presence of calcium and prothrombin (28,29), and a LAC IgG preparation can enhance the binding of prothrombin to endothelial cells and increase thrombin generation on these cells (45), suggesting that APT may concentrate prothrombin on cell surface phospholipids and thus lead to a hypercoagulable state.…”
Section: Pathogenic Role Of Aptsmentioning
confidence: 99%
“…44). ␤ 2 GPIdependent aPL may cause atherosclerosis by direct activation of the vascular endothelium (40,45,46), increased clearance of oxidized LDL (36), or reduced paraoxonase activity, leading to increased oxidation of LDL (47).…”
Section: Molecular Structure and Function Of ␤ 2 Gpimentioning
confidence: 99%